THE INFLUENCE OF COOPERATIVE LEARNING MODELS TO INCREASE LEARNING MOTIVATION ON OBJECT-ORIENTED PROGRAMMING MATERIALS - Zega, Imanuel; Rondonuwu, Yeremia Victor; Hardiyanti, Mawar; Sarumaha, Demonius (Educational Technology Journal, 2024)
The world of education requires an interesting learning process for students, with the aim that the students being taught do not feel bored in following the learning process. Learning methods that use conventional methods are one of the causes of students feeling bored in the learning process. The research carried out was Classroom Action Research (PTK) with a cooperative learning model applied to third-semester students in the Information Systems study program at Unversitas Pignatelli Triputra. Cooperative learning is a teaching method that involves students studying in small groups to achieve common goals when completing assignments. It is based on the idea that when students work together and exchange knowledge, they learn more effectively. Based on the results of the data analysis that has been carried out, it is known that the initial reflection scores achieved by students were only 22.2% of students who achieved completeness, 55.5% in cycle I and cycle II, and as much as 83.3%. This shows that the use of appropriate teaching strategies can produce real improvements and help students learn enthusiastically and achieve the desired goals.